Coronavirus Disease-2019 (COVID-19): An Updated Review - Rudrapal, Mithun; Khairnar, Shubham J.; Borse, Laxmikant B.; Jadhav, Anil G. (Drug Research, 2020)
The current outbreak of novel Coronavirus Disease-2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a major pandemic situation and a catastrophe for humans. COVID-19 is a severe infectious disease particularly of the respiratory system characterized by fatal complications such as severe acute respiratory distress syndrome (SARS), pneumonia, cardiac arrhythmia, kidney failure/ multiple organ failure and even death. Since its discovery, the SARS-CoV-2 has spread across 213 countries or territories, causing more than 8.5 million people with a rising death toll over 5.5 million people (as of June 2020, WHO). In fact, the current looming crisis of COVID-19 has become an increasingly serious concern to public health. It has affected lives of millions of people with severe impact on health systems and economies globally. Since there are no specific drugs and/or vaccines available so far, combating COVID-19 remains to be a major challenging task. Therefore, development of potential and effective treatment regimens (prophylactic/therapeutic) is urgently required which could resolve the issue. In this review, we summarize the current knowledge about the coronavirus, disease epidemiology, clinical manifestations and risk factors, replication of the virus, pathophysiology and host immune responses of SARS-CoV-2 infection. The therapeutic interventions and prophylactic measures along with precautionary measures are the frontline approaches that could be undertaken in order to control and prevent the spread of the deadly and highly contagious COVID-19 are also detailed herein.
Keywords: Coronavirus; COVID-19; SARS-CoV-2; Pneumonia; Respiratory infection; Anti-retrovial